2017
DOI: 10.1007/s10934-017-0526-7
|View full text |Cite
|
Sign up to set email alerts
|

Ni- and CuNi-modified activated carbons and ordered mesoporous CMK-3 for furfural hydrotreatment

Abstract: Author prepared the catalysts, planned the experimental work together with RK and JL, characterized the catalysts excluding atomic adsorption spectroscopy, performed the planned experiments, wrote the first version of the manuscript and after discussions with RK and JL, wrote the final version of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 125 publications
0
6
0
Order By: Relevance
“…Moreover, the AC‐B supported Pt catalyst produced 1.7 % FMA whereas with the AC‐S support, no FMA was produced. The formation of this relatively large condensation product was noticed to be favored by large pores by Jaatinen et al . The 3Pt/AC‐B catalyst had more mesopores than the 3Pt/AC‐S catalyst (Table ), which could explain the formation of FMA; however, no similar behavior was observed with Ru or Ni.…”
Section: Resultsmentioning
confidence: 90%
“…Moreover, the AC‐B supported Pt catalyst produced 1.7 % FMA whereas with the AC‐S support, no FMA was produced. The formation of this relatively large condensation product was noticed to be favored by large pores by Jaatinen et al . The 3Pt/AC‐B catalyst had more mesopores than the 3Pt/AC‐S catalyst (Table ), which could explain the formation of FMA; however, no similar behavior was observed with Ru or Ni.…”
Section: Resultsmentioning
confidence: 90%
“…In our previous study, monometallic Ni catalysts are less active than noble metals, leading to the maximum MF yield of less than 40% [49]. However, the addition of Cu is known to significantly increase the catalytic activity of Ni [11,43]. Gong et al [31] have reported the beneficial combination of CuOx and Cu species on AC for MF production.…”
Section: Conversion Of Furfural To 2-methylfuranmentioning
confidence: 95%
“…Prior to metal addition, the activated support materials were further washed with HNO3 and H2SO4 to modify their surface properties. The combination of Cu and Ni was selected as these metals were found to be beneficial for the hydrotreatment of furfural to produce MF [11,12,43].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with single metal catalysts, bimetallic catalysts have unique synergistic effect, which may improve the activity and stability of catalysts. [84,86,88,90,[93][94][95]99,[101][102][103][104] The main synergistic effect of bimetallic catalysts is to enable the generation of new reaction sites [77][78][79]83,85,[96][97][98]105] and promote charge transfer. [87,91,96,97,106] The active sites can be geometrically and electronically modified by the above effects, and ultimately regulate their catalytic properties.…”
Section: Synergistic Effect Of Bimetalmentioning
confidence: 99%
“…Compared with single metal catalysts, bimetallic catalysts have unique synergistic effect, which may improve the activity and stability of catalysts [84,86,88,90,93–95,99,101–104] . The main synergistic effect of bimetallic catalysts is to enable the generation of new reaction sites [77–79,83,85,96–98,105] and promote charge transfer [87,91,96,97,106] .…”
Section: Bimetallic Catalyst Supported On Carbonmentioning
confidence: 99%